Steroid responsiveness in connective tissue diseases. - Gaston, H. (1983)
Thirty-four patients with connective tissue disease used dexamethasone drops 0.1% in one eye for 6 weeks. There was a higher incidence of positive steroid response than would be expected in a normal population. Most of the male patients were responders. Care should be exercised when prescribing local steroids for these patients. Males should be offered regular screening for glaucoma.